(untitled) (Research, Society and Development, 2018)
The present study aims to analyze the studies that address the implementation of the Articulated Actions Plan (PAR), published in the period from 2009 to 2016, identifying in them the results that point to this tool as an instrument for the induction of public policies by the Central Government. The study is part of the bibliographic survey of the Research Project "Regulation and Implementation of the National Education System in Brazil: Intergovernmental Relations for the Guarantee of the Right to Education", a project funded by CNPq, in an initiative of the Federalism Research Group and Educational Policies "Of the Graduate Program of the Education Center of the Federal University of Espírito Santo. Among the 28 works found on the PAR theme, in this time cut and publication vehicles, 23 indicated induction characteristics in the implementation of PAR in counties of several states of the federation, and the action was largely consolidated vertical form directly from the central government to the municipalities, without state intermediation. These observations refer to the discussions on coordination, cooperation and collaboration, and also on centralization and decentralization, which historically go through the whole debate about the nature of Brazilian federalism.